Critical analysis of early and late outcomes after isolated coronary artery bypass surgery in elderly patients - Saxena, A.; Dinh, D.; Yap, C.; Reid, Christopher; Billah, B.; Smith, J.; Shardey, G.; Newcomb, A. (2011)
Background: The proportion of elderly (≥80 years) patients undergoing coronary artery bypass surgery (CABG) is increasing. Methods: A retrospective analysis of data, collected by the Australasian Society of Cardiac and Thoracic Surgeons Cardiac Surgery Database Program between June 2001 and December 2009 was performed. Isolated CABG was performed in 21,534 patients; of these, 1,664 (7.7%) were at least 80 years old (group 1). Patient characteristics, morbidity, and short-term mortality of these patients were compared with those aged less than 80 years (group 2). The long-term outcome of group 1 patients after CABG surgery was compared with an age and sex-matched Australian population. Results: Patients over 80 years old were more likely to be female (36.6% vs 17.3%, p < 0.001) and presented significantly more often with heart failure, hypertension, and triple-vessel disease (all p < 0.05). The 30-day mortality was higher in group 1 patients (4.2% vs 1.5%, p < 0.001). Group 1 patients also had an increased risk of complications, including prolonged (>24 hours) ventilation (14.2% vs 8.2%, p < 0.001), renal failure (7.3% vs 3.4%, p < 0.001), and mean intensive care unit stay (60.7 vs 42.5 hours, p < 0.001). The 5-year survival of elderly patients (73%) was comparable with the age-matched Australian population. Independent risk factors for 30-day mortality in group 1 patients included preoperative renal failure (p = 0.010), congestive heart failure (p = 0.014), and a nonelective procedure (p = 0.016). Conclusions: Elderly patients who undergo isolated CABG have significantly lower perioperative risks than have been previously reported. The long-term survival of these patients is comparable with an age-adjusted population.